Synthesis, Characterizations and Biological Efficacy of Aminobenzofuran and 2-Methoxyphenylacetaldehyde and Its Co(II) and Zn(II) Complexes - Abdulazeez, Abduljeleel Mohd; Aminu, Ahmad; Ahmad, Aisha (Darul Yasin Al Sys, 2024)
Metal complexes of some transition metal ions viz Co (II), and Zn (II) have been synthesized from a Schiff base (L) formed by the condensation of 2-amino-benzofuran and 2-methoxyphenylacetaldehyde. Synthesized compounds have been studied by various spectroscopic techniques and eval_uated for their biological efficacy. From the FTIR result, A peak at 1566 cm-1 was assigned to azomethine v(C=N) stretching vibration, which shifted to 1640cm-1 and 1637cm-1 in cobalt (II) and, zinc (II) complexes respectively. Also, a broad band was observed in the Schiff base and the complexes at 3219cm-1 which indicate presence of water of crystallization to the complex structure. The complexes are non-electrolytic in nature and have high thermal stability. Job’s method of continuous variation suggests 1:2 metal to ligand ratio. Antibacterial and antifungal study of ligand and its metal complexes have shown that the metal complexes are more active than their corresponding ligand.